Infrastructure and Resources of Private Schools in Cali and the Implementation of the Bilingual Colombia Program - Norbella Miranda; Ángela Patricia Echeverry (Asociación Colombiana de Profesores de Ingles, 2010)
Institutional factors affect the implementation of educational policies. Physical school infrastructure and the availability of resources determine to a certain extent whether a policy may be successfully transformed into practice. This article provides a description and analysis of school infrastructure and resources of private institutions of strata 1-4 in Cali and how these two factors relate to the implementation of the Bilingual Colombia Program (BCP). In general, it was found that schools were alike regarding the availability of general resources and the inadequate condition of some infrastructure aspects. Yet, significant gaps among schools were found in the availability and number of specialized resources for English language teaching. Results suggest that additional resources might need to be allocated in schools for a successful implementation of the BCP.